Do social media campaigns foster vaccination adherence? A systematic review of prior intervention-based campaigns on social media. (January 2023) - Argyris, Young Anna; Nelson, Victoria R.; Wiseley, Kaleigh; Shen, Ruoyu; Roscizewski, Alexa
Highlights: We conducted a systematic review of six databases to examine whether social media campaigns foster vaccine adherence. Out of 92 vaccination interventions that employed media, only 15 were conducted on social media. Most of these 15 campaigns failed in increasing vaccination rates among the audiences. Few of these 15 campaigns used measures specifically designed to assess the effectiveness of social media campaigns. Nearly half of these 15 campaigns did not adopt critical success factors for social media campaigns. Abstract: The COVID-19 pandemic has demonstrated the importance of large-scale campaigns to facilitate vaccination adherence. Social media presents unique opportunities to reach broader audiences and reduces the costs of conducting national or global campaigns aimed at achieving herd immunity. Nonetheless, few studies have reviewed the effectiveness of prior social media campaigns for vaccination adherence, and several prior studies have shown that social media campaigns do not increase uptake rates. Hence, our objective is to conduct a systematic review to examine the effectiveness of social media campaigns and to identify the reasons for the mixed results of prior studies. Our methodology began with a search of seven databases, which resulted in the identification of 92 interventions conducted over digital media. Out of these 92 studies, only 15 adopted social media campaigns for immunization. We analyzed these 15 studies, along with a coding scheme we developed based on reviews of both health interventions and social media campaigns. Multiple coders, who were knowledgeable about social media campaigns and healthcare, analyzed the 15 cases and obtained an acceptable level of inter-coder reliability (> .80). The results from our systematic review show that only a few social media campaigns have succeeded in enhancing vaccination adherence. In addition, few campaigns have utilized known critical success factors of social media to induce vaccination adherence. Based on these findings, we discuss a set of research questions that informatics scholars should consider when identifying opportunities for using social media to resolve one of the most resilient challenges in public health. Finally, we conclude by discussing how the insights drawn from our systematic reviews contribute to advancing theories, such as social influence and the health belief model, into the realm of social media–based health interventions.